Strained Presidentialism: Institutional Design and Persistent Crises in Peru (2016–2020) - Barandiarán Argote, Alonso (2025)
In recent years, Peru has faced a political crisis marked by continuous clashes between the Executive and Legislative branches, particularly during the 2016-2020 period. These conflicts led to various institutional responses—such as impeachments, dissolutions, and resignations—that, rather than resolving the crisis, contributed to its prolongation. This cycle of instability culminated in a wave of social unrest, expressed through mass protests and the resignation of then-president Manuel Merino. This study argues that the weakness of Peru’s presidential model, reflected in its institutional design and its limited capacity to manage presidential crises, facilitated the persistence of the Executive-Legislative conflict during the 2016-2020 period. Through the process tracing method, this research reconstructs key events and analyzes information from primary and secondary sources to understand the factors that perpetuated the crisis. The study concludes that the combination of a presidential system with weak institutions, the fragmentation of the party system, and the strategic use of political control mechanisms have deepened instability, generating recurring crises without providing structural solutions.